Synapse-specific roles for microglia in development: New horizons in the prefrontal cortex - Blagburn-Blanco, Sara V.; Chappell, Megan S.; De Biase, Lindsay M.; DeNardo, Laura A. (Frontiers in Molecular Neuroscience, 2022)
Dysfunction of both microglia and circuitry in the medial prefrontal cortex (mPFC) have been implicated in numerous neuropsychiatric disorders, but how microglia affect mPFC development in health and disease is not well understood. mPFC circuits undergo a prolonged maturation after birth that is driven by molecular programs and activity-dependent processes. Though this extended development is crucial to acquire mature cognitive abilities, it likely renders mPFC circuitry more susceptible to disruption by genetic and environmental insults that increase the risk of developing mental health disorders. Recent work suggests that microglia directly influence mPFC circuit maturation, though the biological factors underlying this observation remain unclear. In this review, we discuss these recent findings along with new studies on the cellular mechanisms by which microglia shape sensory circuits during postnatal development. We focus on the molecular pathways through which glial cells and immune signals regulate synaptogenesis and activity-dependent synaptic refinement. We further highlight how disruptions in these pathways are implicated in the pathogenesis of neurodevelopmental and psychiatric disorders associated with mPFC dysfunction, including schizophrenia and autism spectrum disorder (ASD). Using these disorders as a framework, we discuss microglial mechanisms that could link environmental risk factors including infections and stress with ongoing genetic programs to aberrantly shape mPFC circuitry.